Transverse Deflection of a Cold-Worked Metal Plate Clamped Around Its Edge - Bish, R.L. (Engineering Transactions, 1995)
New principles are applied in an investigation of the general problem of a sheet of cold-rolled metal, clamped around its rim and displaced transversely. For the particular case of a circular cold-worked metal sheet clamped at its edge and displaced transversely at its centre by a flat-ended circular punch, it is predicted that the deflection will vary in proportion to the logarithm of radial distance from the punch axis, and that circles engraved on the sheet, concentric with the punch, will neither expand nor contract during deformation, while the punching load will remain proportional to the punch displacement and inversely proportional to the logarithm of the ratio of the clamp and punch diameters.